Análise da satisfação dos usuários de infraestrutura urbana: caso de vias públicas com pavimento anti-pó e pavimento em concreto asfáltico no município de Curitiba - Rocha, Edson Maikon Da (2017)
The growing concern with environmental issues means that many processes are reviewed in order to minimize impacts to nature and in this sense, one of the ways to take advantage of waste is the recycling that, through the reprocessing of objects, makes it possible to make new products. The present research results from a study of the user satisfaction analysis of the Black-Top and final pavement applied in the streets of the city of Curitiba - PR, to ensure if the technology of pavement recycling in the restoration of low traffic streets, using Technology for the recycling of in situ works of granular bases, has been satisfactory. The investigations in the urban roads that were recycled in the year 2012, counted on a sample composed by 130 inhabitants of 7 different districts. The previous accomplishment of a bibliographical revision aided the understanding about the pavement and the recycling of pavements. For the application of the research the multimethod was used, with quantitative and qualitative data, developing a descriptive exploratory research that had the application of a structured survey questionnaire. Through the processing of the data collected by the questionnaire, it was possible to estimate the main problems attributed to the two types of pavements, the importance of the improvements and the degree of satisfaction of the local users. The results indicate that the Black-Top did not fulfill its original role of preventing the formation of mud and dust. On the other hand, the recycling procedure was very effective, reaching the satisfaction of 90% of the users interviewed. Within this survey, a negative aspect of the recycling of the road that was the insecurity factor was determined, since, the speed increased as a consequence of the improvement of the pavement. Thus, it was observed that the recycling of pavements is a necessary procedure for the survival of the asphalt, and that benefits such as the improvement in the flow of vehicles, the valuation of real estate and the reduction of complaints with structural, health and environmental problems environment.